2019
DOI: 10.12669/pjms.35.1.93
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Hypocalcaemia following Total Thyroidectomy

Abstract: Background & Objective: Patients who undergo Total thyroidectomy are at higher risk for postoperative hypocalcaemia, which can lead to significant short and long term morbidity. The aim of this study was to determine the frequency of postoperative hypocalcaemia undergoing Total thyroidectomy. Methods: A total of 854 patients who underwent Total thyroidectomy and completion thyroidectomy between January 2003 to December 2016 at Endocrine Surgical unit, Jinnah Postgraduate Medical Centre, Karachi, were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 16 publications
0
16
2
Order By: Relevance
“…This is in contrast to previous studies, which have shown that patients with malignant conditions are more likely to develop hypocalcemia. 2,14 Nevertheless, a literature review has indicated that the prevalence of hypocalcemia was higher among patients with benign thyroid disease, which might be due to the increase in size and vascularity of the thyroid gland associated with benign diseases, such as graves and multinodular goiter, which may cause difficulties during operation. 13 However, other studies have illustrated that malignant conditions were more likely to be associated with a comorbid hypocalcemia.…”
Section: Disclosurementioning
confidence: 99%
See 3 more Smart Citations
“…This is in contrast to previous studies, which have shown that patients with malignant conditions are more likely to develop hypocalcemia. 2,14 Nevertheless, a literature review has indicated that the prevalence of hypocalcemia was higher among patients with benign thyroid disease, which might be due to the increase in size and vascularity of the thyroid gland associated with benign diseases, such as graves and multinodular goiter, which may cause difficulties during operation. 13 However, other studies have illustrated that malignant conditions were more likely to be associated with a comorbid hypocalcemia.…”
Section: Disclosurementioning
confidence: 99%
“…13 However, other studies have illustrated that malignant conditions were more likely to be associated with a comorbid hypocalcemia. 2,14 The plausible underlying mechanism might be related to the attachment and fusion of the thyroid capsule and the parathyroid glands, which might be damaged during CCND. 15 Additionally, a retrospective study showed that CCND might increase the risk of hypocalcemia following TT, and there is a significant association between CCND and hypocalcemia (p=0.049).…”
Section: Disclosurementioning
confidence: 99%
See 2 more Smart Citations
“…The overall incidence in this study is on the lower side of the reported data in the literature; more significantly, we have achieved the lowest possible rate of permanent hypocalcemia. 23,24 Recurrent laryngeal nerve palsy may be the result of a number of iatrogenic injury mechanisms. For instance, it may be caused by direct section, thermal injury by cautery or by suture entrapment of the nerve.…”
Section: Srmentioning
confidence: 99%